Peran Manajemen Risiko Dalam Meningkatkan Keselamatan Pasien di Fasilitas Kesehatan - Artyani Putri Binta (PT. Hasba Edukasi Mandiri, 2025)
Patient safety is one of the main aspects of healthcare services that must be considered to prevent harmful medical incidents. Risk management is an effective approach to identifying, analyzing, and mitigating potential hazards in healthcare facilities. This study employs a literature review method to analyze risk management strategies in enhancing patient safety. The findings indicate that the implementation of risk identification and mitigation systems, healthcare worker training, the utilization of technology such as electronic medical records, and a transparent incident reporting system can significantly reduce potentially harmful events for patients. However, the implementation of these strategies still faces several challenges, such as a lack of awareness among medical personnel, infrastructure limitations, and obstacles in changing the culture of safety in the workplace. Therefore, collaboration between medical personnel, hospital management, and the government is crucial to ensuring the effectiveness of risk management implementation in healthcare facilities. With the right strategies and commitment from various stakeholders, patient safety can be continuously improved, leading to safer and higher-quality healthcare services.